2015
DOI: 10.15446/caldasia.v37n2.53867
|View full text |Cite
|
Sign up to set email alerts
|

CAMBIOS EN LA COMPOSICIÓN DE LÍQUENES EPÍFITOS RELACIONADOS CON LA CALIDAD DEL AIRE EN LA CIUDAD DE LOJA (Ecuador).

Abstract: RESUMENA pesar de que la contaminación del aire constituye uno de los principales problemas en la ciudad de Loja, actualmente no existe una estrategia para monitorear las emisiones de contaminantes. Los líquenes epífitos han sido ampliamente utilizados como bioindicadores de la contaminación atmosférica, debido a que obtienen la mayor parte de nutrientes del aire, lo que los hace muy sensibles a los cambios derivados de la contaminación. Se evaluó la calidad del aire en siete parques de la ciudad, donde se reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
(11 reference statements)
1
14
0
9
Order By: Relevance
“…The climate is humid tropical with a mean annual temperature between 7-20 °C, and annual rainfall between 800-2500 mm [38]. Since the 1960s, these native forests have been transformed into agricultural and urbanized land [31,36,37]. In this study, we distinguished four different land uses, i.e., forest, a combination of forest and pasture, pasture, and urban land use, where we established 12 sampling sites located in riparian margins influenced by those land uses mentioned before.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The climate is humid tropical with a mean annual temperature between 7-20 °C, and annual rainfall between 800-2500 mm [38]. Since the 1960s, these native forests have been transformed into agricultural and urbanized land [31,36,37]. In this study, we distinguished four different land uses, i.e., forest, a combination of forest and pasture, pasture, and urban land use, where we established 12 sampling sites located in riparian margins influenced by those land uses mentioned before.…”
Section: Study Areamentioning
confidence: 99%
“…As a general pattern, microclimatic variables (e.g., light, humidity, and temperature) that change in response to ecosystem transformation have been considered as constraining factors over the taxonomic and functional diversity of epiphytic lichens [21,25]. Therefore, several studies have used both taxonomic and functional diversity (e.g., richness of each functional trait) as indicators of landuse change [20,22,26,27], forest disturbance [14,21,28], global warming [29] and air quality [19,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…En términos generales, el conocimiento de la diversidad de los líquenes epífitos proporciona evidencia sustantiva para la conservación a escala de paisaje (Li, et al, 2013;Estrabou, et al, 2014). Por su parte, Physciaceae y Arthoniaceae, las familias con mayor abundancia y diversidad de especies en el bosque, poseen una amplia distribución geográfica y alta tolerancia frente a las perturbaciones (Soto & Bolaños, 2010;Ochoa, et al, 2015), y colonizan en una amplia variedad de formaciones vegetales en el Trópico (Herrera, et al, 2014) Figura 5. Análisis de componentes principales de la relación entre variables microambientales y especies de líquenes la familia Parmeliaceae hace parte de la diversidad liquénica del bosque y se ha reportado en un amplio rango de hábitats con abundantes géneros y especies (Leavitt, et al, 2015) en el Neotrópico (Rincón, et al, 2011;Rosabal, et al, 2012a), especialmente en las formaciones vegetales andinas y subandinas (Aguirre, 2008).…”
Section: Resultsunclassified
“…In Ecuador, only one active biomonitoring study has been conducted using mosses as indicators of air pollution in the city of Quito [ 35 ], where the authors found the presence of lead and cadmium related to vehicular traffic, but the identification of the species used was not realized. On the other hand, air quality monitoring studies have been carried out in the city of Loja using lichens and bromeliads [ 36 , 37 ]. These studies have shown that urban areas have lower species diversity and a higher accumulation of metals compared to control zones.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aims to determine the air quality of the city of Loja by transplanting three species of mosses ( Rhacocarpus purpurascens , Sphagnum sp. and Thuidium delicatulum ) due to the fact that urban areas of the city of Loja, Ecuador have high levels of air pollution (e.g., metals) related to vehicular traffic [ 36 , 37 ]. We hypothesized that increased urbanization and vehicular traffic towards the center of the city will result in increased bioaccumulation of heavy metals in transplanted mosses.…”
Section: Introductionmentioning
confidence: 99%